Qualitative Spatial Abstraction in Reinforcement Learning - Frommberger, Lutz (Springer, 2012)
Reinforcement learning has developed as a successful learning approach for domains that are not fully understood and that are too complex to be described in closed form. However, reinforcement learning does not scale well to large and continuous problems.